Penerapan Manajemen Perkantoran Dalam Meningkatkan Pelayanan Administrasi Pendidikan Di Mts Yp. Ummul Quraa Tembung, Kec. Percut Sei Tuan, Kab. Deli Serdang, Sumatera Utara, Medan - Tengku Darmansah; Azra Humaira; Fatin Syahirah; Salwa Nabila Damanik; Salwa Putri Verhan (Transformasi: Journal of Economics and Business Management, 2024)
The aim of this study is to elucidate the application of office management in enhancing educational administrative services at MTs Yp. Ummul Quraa. The method utilized in this research is descriptive research using a qualitative approach. Data were gathered through interviews, observations, and documentation. The findings of this study demonstrate that the implementation of office management at MTs Yp. Ummul Quraa is clearly evident. Concrete evidence is observed in the organization of office space, employee discipline control, efforts to strengthen communication with all relevant parties, including administrative staff, students, and alumni, as well as the completion of tasks according to each employee’s responsibilities. Additionally, thorough planning in procuring office equipment and administrative supplies also supports the smooth flow of all administrative activities. Furthermore, customer satisfaction with the administrative services at MTs Yp. Ummul Quraa has met the expected quality standards, reflecting satisfactory service quality. These findings are consistent with the principles of customer satisfaction according to Philip Kotler, which encompass physical evidence, responsiveness to needs, reliability, empathy, and assurance.